2020
DOI: 10.1002/prep.202000221
|View full text |Cite
|
Sign up to set email alerts
|

On the Pressure Generated by Thermite Reactions Using Stress‐Altered Aluminum Particles

Abstract: This study examines pressure build-up and decay in thermites upon impact ignition and interprets reactivity based on the holistic pressure history. The thermite is a mixture of aluminum (Al) combined with bismuth trioxide (Bi 2 O 3) powder. Four different Al particles sizes were examined that ranged from 100 nm to 18.5 μm mean diameter and for each size, two different Al powder treatments were examined: stress-altered compared to untreated, as-received Al powder. Stress-altered Al powders have been shown to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…As for some applications, is desirable to lower the ignition temperature, much research effort is dedicated to the increase of Al ignitability and decrease of its ignition temperature. For example, Williams and Pantoya [14] modified the Al particles reactivity by modifying the Al-Al2O3 core-shell microstructure through annealing and quenching of the powder, to vary interfacial strain and associated stress. Correlation between altering the Al microstructures by stress and lowering ignition point was also observed in [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…As for some applications, is desirable to lower the ignition temperature, much research effort is dedicated to the increase of Al ignitability and decrease of its ignition temperature. For example, Williams and Pantoya [14] modified the Al particles reactivity by modifying the Al-Al2O3 core-shell microstructure through annealing and quenching of the powder, to vary interfacial strain and associated stress. Correlation between altering the Al microstructures by stress and lowering ignition point was also observed in [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The coexistence of two regimes of Al particle combustion, i. e., the existence of two different characteristic burn times for the same particle diameter, explains results on the performance enhancement upon various metal particle treatments for the same particle size [19,20,21]. Successful treatment leads to preferential combustion of particles at shorter times, i. e., an increase in the fraction of particles burning in the fast regime.…”
Section: Burn Time Of Metal Particles: What We Really Get From Experi...mentioning
confidence: 89%
“…The thermal processing of Al powder, specifically its annealing followed by fast quenching had been developed by Hill et al [19]. A number of subsequent studies further demonstrated distinctly different performance of as-received (i. e., called UN, untreated) and thermally processed (i. e., called SQ, super-quenched) powders in different energetic formulations [20,21,23]. Thermal processing the powder resulted in high internal particle stress [19,23], but a link to the mechanism for performance variation remained unclear.…”
Section: Effect Of Thermal Processing Of Al Powder On the Materials R...mentioning
confidence: 99%
“…This has led to the pursuit of various physical or chemical modifications of Al–Al 2 O 3 core–shell microstructure, aiming to lower aluminum’s ignition temperature and consequently enhance the thermite ignition and combustion. In addition, thermal and plasma pretreatments in Al microstructures have shown to lower the initiation onset and the burn time. Because mass transport is a key factor in setting the reaction pathway and hence regulating the ignition point, several other studies have been populated by approaches modifying the native Al 2 O 3 using a polymeric material , or different oxides. , While all of these strategies prove to be categorically effective, it is undeniable that they necessitate time-consuming and cost-ineffective engineering efforts.…”
Section: Introductionmentioning
confidence: 99%